Stiff-Person syndrome: A rare neurological disorder - Mandal, Amit; Thomas, Nihal; Thirumal Appaswamy, Prabhakar (Indian Journal of Case Reports, 2024)
The Stiff-person syndrome (SPS) is an uncommon disorder characterized by progressive rigidity, muscle stiffness, and spasm involving the axial muscles, resulting in severe impairment of ambulation. We present the case of a 49-year-old gentleman with recent onset of progressive asymmetric spastic ataxia, subsequently diagnosed with SPS.